2019
DOI: 10.3390/su11020419
|View full text |Cite
|
Sign up to set email alerts
|

Integrating a Hybrid Back Propagation Neural Network and Particle Swarm Optimization for Estimating Soil Heavy Metal Contents Using Hyperspectral Data

Abstract: Soil heavy metals affect human life and the environment, and thus, it is very necessary to monitor their contents. Substantial research has been conducted to estimate and map soil heavy metals in large areas using hyperspectral data and machine learning methods (such as neural network), however, lower estimation accuracy is often obtained. In order to improve the estimation accuracy, in this study, a back propagation neural network (BPNN) was combined with the particle swarm optimization (PSO), which led to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…For this purpose, several methods, such as correlation analysis, VIF, and random forest are available. Studies have also shown that the Boruta algorithm exhibits superior performance with a higher accuracy and smaller error rate compared to the conventional statistical methods [32,43,51]. However, in our experiment it was also found that there was collinearity among the spectral variables selected by the Boruta algorithm.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…For this purpose, several methods, such as correlation analysis, VIF, and random forest are available. Studies have also shown that the Boruta algorithm exhibits superior performance with a higher accuracy and smaller error rate compared to the conventional statistical methods [32,43,51]. However, in our experiment it was also found that there was collinearity among the spectral variables selected by the Boruta algorithm.…”
Section: Discussionsupporting
confidence: 43%
“…As a commercially developed area, Guangdong has abundant naturally occurring non-ferrous metals and rare metal resources, and has become one of the most heavily contaminated areas in China. In the area, 65 training soil samples (black points in Figure 1) and 15 validation soil samples (cyan points in Figure 1) were collected and located using the global positioning system (GPS) during 22-24 June 2015 [32]. The study area for testing the optimal hyperspectral estimation models was located in the Conghua district of Guangzhou city, Guangdong (Figure 2a).…”
Section: Study Area and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Zheng et al [12] suggested that it is feasible to predict AS element contents in soils using reflectance spectral, and the model results of 4 nm + multiplicative scatter correction (MSC) + partial least squares regression (PLSR) were the best (R 2 = 0.711, residual predictive deviation (RPD) = 1.827); Cheng et al [13] reported that AS contents in surface soils were detectable using visible/near-infrared spectral, and Savitzky-Golay (SG)+PLSR had the best effect (R 2 = 0.75, RPD = 1.81). Many previous studies have investigated models for the estimation of AS content from visible and neat infrared (VNIR) hyperspectral [12][13][14][15][16][17][18][19][20]. PLSR was usually chosen as the estimation model [20].…”
Section: Introductionmentioning
confidence: 99%
“…There are also many methods for evaluating heavy metal pollution; traditional methods such as the pollution index method, the enrichment index method, the Nemerow index method, and the ecological risk index method have been widely used [24]. New intelligent methods such as neural networks have also been used in heavy metal pollution research [25]. Some scholars have proposed an modified eco-risk assessment method, and based on the cost-effective effects of relevant decision makers, proposed a risk-based comprehensive risk management policy [26,27].…”
Section: Introductionmentioning
confidence: 99%